CHARAKTERYSTYKA SYNTAKTYCZNA PLIKÓW POMOCY UKRAIŃSKIEJ WERSJI PAKIETU MICROSOFT OFFICE - Jóźwikiewicz, Przemysław (Studia Ukrainica Posnaniensia, 2016)
The paper presents the syntactic structure of help fi les of the Ukrainian version of Microsoft Office software. The sentence centres are usually predicate words можна, потрібно, слід, modal predicates, impersonal constructions -но, -то, including their complex forms (було ввімкнено, має бути установлено, повинно бути обладнано); very frequent are clauses of purpose and conditional clauses. Help fi les are also characterised by a magnitude of compound-complex sentences (also including the imperative forms), questions and structures which contain salutations.